Exploring the Relationship Between Artificial Intelligence, Autonomous Learning, and Skills Required for Success in The 21st Century (2024)
Objective:The topic of this study focuses on how autonomous learning enhances 21st century competencies through the use of artificial intelligence and educational technologies. The objective is to explore the relationship between autonomous learning, artificial intelligence and 21st century competencies.Theoretical Framework:The main concepts and theories underpinning the research were: artificial intelligence in education, autonomous learning and 21st century skills.Method:The methodology adopted for this research was a systematic mapping of 991 scientific articles published in the last ten years in three databasesResults and Discussion: The results obtained revealed that artificial intelligence is still in its infancy in the use of data and machine learning systems, until its impact on society as a whole is better understood. Likewise, critical thinking, collaborative work and problem solving are the competencies that show a strong relationship with both autonomous learning and artificial intelligence.Research implications:the main fields of study were: self-regulated learning, 21st century competencies and their relationship with artificial intelligence. The impact could be seen in the educational, economic, environmental and social sectors.